2016
DOI: 10.1161/circulationaha.115.020279
|View full text |Cite
|
Sign up to set email alerts
|

Gait Speed Predicts 30-Day Mortality After Transcatheter Aortic Valve Replacement

Abstract: Gait speed, alone or incorporated into geriatric rating scales, is associated with mortality among community-dwelling individuals, 10 patients with coronary heart disease, 11 elderly patients with heart failure, 12 and those undergoing cardiac surgery, including aortic valve replacement.13 Nevertheless, the association between slow gait speed (which is an indicator of physical frailty) and outcomes after TAVR in US Background-Surgical risk scores do not include frailty assessments (eg, gait speed), which are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(53 citation statements)
references
References 40 publications
2
50
1
Order By: Relevance
“…The importance of subgrouping based on gait speed, especially in TAVR cohorts, has been demonstrated in previous investigations. 15,16 Moreover, a previous report indicated that the optimal marker of frailty in terms of gait speed was a gait speed of <0.57 m/sec, which is close to gait speed <0.5 m/sec and our results of survival CART. 16 Although our cutoff value for gait speed was similar to those in previous investigations, potential ethnic differences should be considered.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The importance of subgrouping based on gait speed, especially in TAVR cohorts, has been demonstrated in previous investigations. 15,16 Moreover, a previous report indicated that the optimal marker of frailty in terms of gait speed was a gait speed of <0.57 m/sec, which is close to gait speed <0.5 m/sec and our results of survival CART. 16 Although our cutoff value for gait speed was similar to those in previous investigations, potential ethnic differences should be considered.…”
Section: Discussionsupporting
confidence: 87%
“…A cutoff point of 0.83 m/sec has been advocated as defining slow walkers for patients undergoing cardiac surgery, 11 whereas a lower cutoff of <0.5 m/sec has been proposed for patients undergoing TAVR, who are typically older and more functionally compromised. 15,16 Therefore, the patients were categorized into 4 gait speed groups as follows: normal walkers (>0.83 m/sec), slow walkers (0.5-0.83 m/sec), the slowest walkers (<0.5 m/sec), and those unable to walk (model 1). The unable-to-walk group included patients who depended on a wheelchair or almost depended for personal care.…”
Section: Gait Speed Assessmentmentioning
confidence: 99%
“…(65) Gait speed predicts short-term mortality and complications after cardiac surgery or TAVR. (6-8) We found a large body of evidence to support use of mobility assessment to predict mortality at ≥6 months after major or minimally invasive procedures and functional status after minimally invasive procedures. Although 6MWT was most frequently evaluated, a simple gait speed or TUG test might be as useful, given its high correlation with 6MWT performance (0.70-0.73).…”
Section: Discussionmentioning
confidence: 99%
“…4,5,7-10,12,18, 22 In this era of newer technology providing safer procedures, we can recognize that the risk following TAVI is getting lower, and so our questions have shifted to not only the causes of deaths but also the quality of life following TAVI. 23 In this analysis, multifaceted rather than simple one-sided, objective rather than subjective, and multi-grade rather than simple few-grade evaluation seemed superior for reflecting frailty and therefore predicting the outcomes following TAVI, because essentially frailty is complex and multifactorial.…”
Section: Discriminatory Performance Of Each Frailty Assessmentmentioning
confidence: 99%